Revolutions, Social Movements, and Contentious Politics - Tilly, Charles (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
This course should help undergraduates who already have a background in social science and/or modern history to think systematically about contentious politics – processes in which people make conflicting collective claims on each other or on third parties – as they participate in them, observe them, or learn about how they are happening elsewhere. We will spend little time reviewing theories of political contention or methods for gathering and analyzing evidence. We will spend most of our time examining how such forms of contention as social movements, revolutions, nationalist mobilization, and ethnic conflict have worked in different times and places, as well as thinking through parallels and differences among them. Most sessions will operate as lecture-discussions.